El sagrado arte de despedirse. Una reflexión sobre el final de la vida y su acompañamiento (Teología, 2020)
The article addresses the subject of death as departure from the standpoint of the spiritualprocess that takes place in such circumstances. Using a biographical testimony,the author examines the experience from the conceptualization of the subject madeby an American author (J. Rupp) in her book Praying our goodbyes and draws someconclusions about this process.
Keywords: Death; Mourning; Prayer; Grieff Process; Farewell.